Performance of novel tissue harmonic echo imaging using endoscopic ultrasound for pancreatic diseases - Matsumoto, Kazuyuki; Katanuma, Akio; Maguchi, Hiroyuki; Takahashi, Kuniyuki; Osanai, Manabu; Yane, Kei; Kin, Toshifumi; Takaki, Ryo; Matsumori, Tomoaki; Gon, Katsushige; Tomonari, Akiko; Nojima, Masanori (Endoscopy International Open, 2016)
Background and study aims: Recently, tissue harmonic echo (THE) imaging has advanced with the development of a new endoscopic ultrasound (EUS) monitor/processing unit. With this new technology, penetration (THE-P) and resolution (THE-R) images can be obtained. The aim of this study was to investigate the performance of this novel THE imaging using a new processing unit for pancreatic diseases.Patients and methods: Fifty patients with pancreatic lesions (38 cystic, 12 solid) were retrospectively analyzed. At each examination, 3 EUS images of the same pancreatic lesion were obtained using B-mode, THE-P mode, and THE-R mode imaging. Each set of EUS images was randomly arranged and evaluated independently by 4 physicians blinded to the imaging technique. Images were compared using a Likert scale 5-point grading system for each parameter.Results: For cystic lesions, THE-P mode images were significantly superior to conventional B-mode images for visualizing the boundary, septum, nodules, and total image quality (P < 0.05). THE-R mode images were significantly superior to conventional B-mode images for visualizing the boundary, septum, and total image quality (P < 0.05). However, for solid lesions, there was no significant difference in all the evaluation points between THE-P and conventional B-mode images. THE-R mode images were inferior to conventional B-mode images for visualizing the boundary, internal structure, and total image quality (P < 0.05). Conclusions: For pancreatic cystic lesions, THE mode images provided better lesion characterization than conventional B-mode images. Further research is required to determine if this improvement will result in improved EUS diagnostics.